2017
DOI: 10.3390/su9050763
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Green Supply Chain Integration on Firm Performance: A Contingency and Configuration Perspective

Abstract: This study investigates the impacts of three dimensions of green supply chain integration (GSCI) on operational and financial performance, from both a contingency and a configuration perspective. From the contingency perspective, we used hierarchical regression to determine the impacts of individual GSCI dimensions (green internal, customer and supplier integration) and their interactions on firm performance. From the configuration perspective, we used cluster analysis to develop patterns of GSCI, which were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 49 publications
2
46
1
Order By: Relevance
“…The major purpose of green supplier integration is to solve environmental problems jointly and reduce the adverse impacts of production and operational processes on the natural environment, which is different from supplier integration in previous studies [6,12]. In the process of green supplier integration, the manufacturer and its suppliers may depend on each other, and the importance of trust becomes more prominent [13][14][15]. Thus, there is a need to investigate the impacts of dependence and trust on green supplier integration.…”
Section: Introductionmentioning
confidence: 99%
“…The major purpose of green supplier integration is to solve environmental problems jointly and reduce the adverse impacts of production and operational processes on the natural environment, which is different from supplier integration in previous studies [6,12]. In the process of green supplier integration, the manufacturer and its suppliers may depend on each other, and the importance of trust becomes more prominent [13][14][15]. Thus, there is a need to investigate the impacts of dependence and trust on green supplier integration.…”
Section: Introductionmentioning
confidence: 99%
“…An important issue confronted in this study dealt with the collection of reliable data concerning green external integration. Many studies used a single informant in studying relationship issues between different organizations [19], while some researchers have demonstrated the benefits of using multiple informants [40]. After visiting ten firms during the pilot test of the questionnaire, we found that an appropriate method was to identify a key informant who is knowledgeable in green supply chain management [41].…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Mutual trust and commitment are important in reducing risks and the opportunistic behaviors related to green supplier integration [19]. For small firms, conflicts between manufacturers and suppliers may exist in the early stage of green supplier integration, influencing the performance outcomes of green supplier integration.…”
Section: Theory Framework and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations